Hepatotoxicity of ICI monotherapy or combination therapy in HCC: A systematic review and meta-analysis - Yuping Lu; Jing Lin; Yufeng Lu; Luping Lin; Shicheng Zheng; Yu Chen; Sha Huang (PLoS ONE, 2025)
Background The aim of this study was to reveal the hepatotoxicity profile of different immune checkpoint inhibitor (ICI) used strategies in patients with Hepatocellular carcinoma (HCC) by meta-analysis. Methods Literature was searched through PubMed, Cochrane, Embase, and Web of Science up to October 14, 2023, and the subject terms were “Carcinoma, Hepatocellular” and “Immune Checkpoint Inhibitors”. The main observations were alanine aminotransferase (ALT) and aspartate aminotransferase (AST). ALT and AST were graded according to CTCAE. Results A total of 32 studies with 7662 patients were included in the analysis. The results of meta-analysis showed that among different ICI treatment regimens, ICI monotherapy had the lowest incidence of any grade of ALT and AST elevation, and the highest for ICI+multikinase inhibitor (MKI); ICI+anti-VEGFR/VEGFA and ICI monotherapy had a lower incidence of grade ≥3 ALT and AST elevations, while ICI + MKI, dual immunotherapy, and dual immunotherapy+MKI had a higher incidence of grade ≥3 ALT and AST elevations; ICI monotherapy was more prone to any grade ALT elevation than placebo, and ICI monotherapy was more prone to ≥ 3 grade AST elevation than MKI; combination immunotherapy was more prone than MKI to any grade ALT and AST elevations; in grade ≥3 ALT and AST elevations, combination immunotherapy was similar to ICI monotherapy and MKI; ICI + MKI was more likely to have grade ≥3 ALT. Conclusion ICI monotherapy was more likely to cause severe hepatotoxicity than MKI. Combination immunotherapy treatment increased the incidence of hepatotoxicity compared to monotherapy, and ICI + MKI was prone to develop severe hepatotoxicity.